ASSISTANCE OF MUSLIM HEALTHCARE WORKERS TO PATIENTS PERFORM WUDU AND PRAY - Shomad, Abdus; Aulia Az-Zahra, Syafira; Farchad Dwi Cahyo, Muhamad; Meydina Azzahra, Faradita; Waez, Abdurrahman; Amiruddin, Muhammad (International Journal of Multidisciplinary Reseach, 2025)
This paper discusses the role of healthcare workers in assisting patients to perform ablution (wudhu) as part of their spiritual needs during hospitalization. In Islam, wudhu is a prerequisite for prayer that must still be observed even in illness. However, patients physical limitations often hinder them from performing wudhu independently, making healthcare assistance essential. This study aims to identify patients ability to perform wudhu, analyze the role of healthcare workers in providing spiritual assistance, and examine the influencing factors. The findings show that healthcare support has a positive impact on patients inner peace, motivation for recovery, and satisfaction with hospital services. Nevertheless, challenges such as heavy workloads, limited understanding of fiqh thaharah, and the lack of hospital policies on spiritual care remain obstacles. Therefore, training and institutional support are needed to integrate spiritual and medical services. The involvement of healthcare workers in assisting wudhu reflects a holistic care model that harmonizes patients physical and spiritual dimensions.